Association of Gut Microbiota Composition with Alzheimer’s-Like Disease in A Rat Model - Heiba, Hana (AUC Knowledge Fountain, 2023)
With many countries turning ‘grey’ and facing an issue with aging populations, the risk of developing one form of neurodegenerative disease is increasing. Dementia, being the most common syndrome resulting from neurodegeneration, severely affects memory and cognitive functions. Alzheimer’s disease (AD) is the most common neurodegenerative disorder, with an estimated 615,000 new cases will be added to the existing 5.7 million by 2030 (Alkasir et al., 2017). In the current study, we establish a sporadic AD-like rat model by injecting STZ intracerebrally. Stool samples were collected at two time points; after three weeks for the acute stage, and 3 months for the chronic stage. Behavioral results show a significant difference in the working memory of the acute and chronic STZ-induced sAD-like rats when compared to age matched control groups. 16S rRNA sequencing on 18 samples revealed that Alpha diversity showed a significant difference between the STZ-induced sAD-like groups and control groups (p-value In conclusion, this project did not align with the reported literature in all aspects, although there was a decrease in the Faith PD alpha diversity index, no significant differences were observed in the beta diversity index and relative abundance of bacteria among the groups. That could be due to the small number of samples used within each group. Future work should increase sample size to produce statistically significant results. In addition, it is advisable to supplement the fecal samples collected from our experimental groups with CSF to add biomarker detection to correlate with bacterial taxa discovered.